Encryption wars shifting tactics. - Caloyannides, M.A (IEEE spectrum)
The growing availability of powerful encryption has in effect rewritten the rule book for creating, storing, and transmitting computer data. People everywhere rightly regard confidentiality as essential for conducting business and protecting personal privacy. But governments worldwide have been sent into a spin, for fear secret encryption keys will add to the weapons of terrorists and other criminals. Some nations have even attempted to control the technology by constructing a maze of regulations and laws aimed at blocking its import, export, and/or use. Such bans have largely failed. The war over encryption has moved beyond controlling the technology itself. Now, some governments are granting law enforcement agencies new powers and funding the development of new tools to get at computerized data, encrypted or otherwise. Rising to that challenge, privacy proponents are striking back with new techniques for hiding data and preserving anonymity in electronic communications. A number of countermeasures have been engineered to augment or replace encryption. Among them are anonymizers, which conceal the identity of the person sending or receiving information, and steganography, which hides the information itself. The paper describes these techniques